Pola Pertumbuhan dan Faktor Kondisi Ikan Famili Nemipteridae di Perairan Pesisir Tapulaga, Sulawesi Tenggara - Asriyana, Asriyana; Rahmawati, Karisma Dwy; Halili, Halili (JSIPi (JURNAL SAINS DAN INOVASI PERIKANAN) (JOURNAL OF FISHERY SCIENCE AND INNOVATION), 2024)
The Nemipteridae family is a fish that lives in demersal areas, especially on the seabed in muddy and sandy areas near coral reefs, both in coastal and offshore waters. This study aims to analyze the growth patterns and condition factors of the Nemipteridae family in the coastal waters of Tapulaga Village, Soropia District, Konawe Regency. Sampling was conducted every two weeks from August to December 2023 with experimental gill nets with mesh sizes of 1, 1 1⁄4, and 1 ¾ inches. The number of fish collected was 423 individuals consisting of two species, namely Saw-jawed monocle bream, Scolopsis ciliata (Lacepède, 1802) 260 individuals, and White-shouldered whiptail, Pentapodus bifasciatus (Bleeker, 1848) 151 individuals. The results showed that most S. ciliata males were found in the 152-160 mm length class (18.03%), while most female fish were found in the 116-124 mm length class (37.68%). P. bifasciatus males were mostly found in the 128-140 mm length class (31.88%), while female fish were mostly found in the 115-127 mm length class (30.49%). Both S. ciliata and P. bifasciatus showed negative allometric growth patterns. Condition factors for male and female S. ciliata ranged from 0.97-1.11 and 0.86-1.17, respectively. For male and female P. bifasciatus, condition factors ranged from 0.83 to 1.13 and 0.85 to 1.11, respectively